Muslims and Christians in Nigeria: A Proposed Solution to Interreligious Violence (Departement of Comparative Study of Religions, 2023)
This article discusses religious violence in Nigeria, particularly the conflict between Islam and Christianity that has been ongoing for about a century. Various factors contribute to this violence, including socio-economic, political, and governance deficits, as well as disputes over religious beliefs or identities. Additionally, the ethnic, religious, linguistic, and cultural diversity in Nigerian society plays a role in escalating the violence. This situation poses a threat to Nigeria's stability and territorial integrity, and the high number of casualties also impacts the country's economy. Numerous primary causes of religious violence in Nigeria include the agitation for the implementation of Sharia law, imbalances in the political and economic systems, extreme interpretations of religion, and external influences. To resolve this conflict, the author suggests several measures that can be implemented by religious leaders. First, they should strive to integrate religious institutions and faith-based organizations. Second, they must avoid conflicts among religious figures and institutions. Third, they should facilitate formal dialogue. Fourth, promote interfaith discussions. Fifth, establish local groups aimed at understanding each other among followers of different religions. And finally, organize conferences, seminars, and open discussions. Conferences and seminars can be held at national and international levels, while open discussions can be broadcasted on national television to reach various layers of Nigerian society, especially vulnerable individuals who could be used or targeted in interfaith conflicts.